Gallstone ileus: a rare case of distal jejunal obstruction - Ahmed, Sajeed; Ghosh, Tamajyoti (International Surgery Journal, 2016)
Gallstone ileus as a cause of distal jejunal obstruction is rare. Herein we present a case of gallstone ileus without any previous biliary symptoms and with Rigler’s triad on radiological investigation. As the signs and symptoms of gallstone ileus is nonspecific high index of suspicion is necessary to make a diagnosis of gallstone ileus. One staged cholecystectomy, fistula repair and enterolithotomy was done and patient recovered uneventfully.